How to Build a Development Section: A Schenkerian Perspective - Timothy Cutler (Gamut: Online Journal of the Music Theory Society of the Mid-Atlantic, 2012)
More than fifty years ago, Allen Forte rightly predicted that the theories of Heinrich Schenker would have a profound impact on music theory pedagogy. In particular, Schenkerian analysis benefits Fernhören (“distance-hearing”), which relates not only to musical connections severed by chronological remoteness, but also to the conceptual space that extends from the composition itself to its background structure. This essay examines one underutilized method for strengthening Fernhören. Using the fundamental structure of an unnamed composition as a starting point, a note or two at a time will be added to the background, working through the middleground and toward the foreground. This procedure is not a methodology for analyzing the tonal structure of music, but instead demonstrates a way to explain a finished analysis. In doing so, the contrapuntal and melodic motivation behind each new pitch is clarified, the aural connection between nonconsecutive events as well as various levels of structure is strengthened, and the identity of the composition becomes evident. Furthermore, this approach addresses the fallacy that Schenkerian analysis represents nothing more than a unidirectional exercise in reduction. This article is part of a special, serialized feature: A Music-Theoretical Matrix: Essays in Honor of Allen Forte (Part II).